Preparation and Application of a Methodology to Obtain a Synthetic Opinion Indicator to Analyse the Context Conditions for the Development of the ICT Sector in Andalusia - García-Tapial Arregui, Joaquín; Crespo-Álvarez, Rocío (Revista de Estudios Andaluces, 2019)
The Andalusian regional government approved on May 16th 2017 the "Strategy to Promote the ICT sector Andalucía 2020”. Linked to the objectives of the TIC2020 strategy, 15 indicators have been defined, which should serve as a basis for evaluating the impact of the Strategy. Among the defined indicators, the so-called "Synthetic Indicator of Conditions of Context of Development of the ICT Sector" is aimed at measuring the contribution of the Strategy to improving the conditions of the business environment for the Andalusian ICT sector. However, the TIC2020 Strategy does not include the method to be followed to obtain this Indicator. Thus, the objective of our research has been to define and apply a methodology for calculating the indicator. For this, a synthetic index based on simple aggregation with equal weights has been defined, for which a methodology based on the Japanese TANKAN index has been designed. As a result of all this, the Synthetic Index has been obtained for the year 2017, with a value of 9.81, as well as a work method that should serve as the basis for obtaining the index during the Strategy period.